The Image of the “Promised Land” in Vladimir Lorchenkov’s Novel “We Will All Be There” (Филологический класс, 2020)
The aim of the article is to analyze the image of the “promised land” on the basis of V. V. Lorchenkov’s literary work “We Will All Be There”. The Moldovan writer, writing in Russian, is actively experimenting with form, language and genre. The postmodern literary paradigm is the starting point for this analysis. The Promised Land, which is derived from biblical texts, in classical literature becomes the designation of the earthly paradise, the corner where man finds happiness. In the novel under analysis, analogies to the biblical topoi (searching for the “promised land”, paradise on earth) are actualized in a typically postmodern spirit. The protagonists of the work – the inhabitants of the village of Larga (Moldovans) – appear as new Jews who left the Egyptian kingdom (Moldova) and went in search of the promised land (Italy), headed by Moses (Seraphim Botezatu). Strange and eccentric inhabitants choose the most incredible ways to fulfil their aspirations to get to the “earthly para- dise” – to blessed Italy. Some try to get there on a tractor converted for this purpose into an airplane, others organize Orthodox crusades into the unclean land of Italy, and still others try to organize a curling team to emigrate to Italy. Plunging into absurdity and some kind of madness, the image of the “promised land” in the artistic space is presented as an earthly paradise, and then as hell, gradually taking on sacrificial blood. The victims of the “promised land” dream can be interpreted not only as a subtle parody of biblical offerings made to God, but also as a sharply satirical image of the contemporary Moldovans’ lifestyle. An ironic rethinking of biblical history, a synthesis of different styles (magical realism, neorealism and socialist realism), absurd plot collisions, when what is funny and absurd turns into a monstrous grotesque, so characteristic of the postmodern spirit, permeate the entire narrative of Lorchenkov. The open finale of the work, devoid of obvious moralizing, leaves the reader, as one might suppose, the right to answer questions related to the future not only of the inhabitants of Larga, but also of the entire “toy” country known as “Moldova”.